THE USE OF THE POWER OF TWO STRATEGIES IN TEACHING READING SKILL TO THE 10TH GRADE STUDENTS - Al-Amin, Muhammad Tias; Herlina; Noviati; Ayesha Fatima Malik; Hassan Ahmed Chaudhry (Esteem Journal of English Education Study Programme, 2025)
This study investigated students' difficulties in communicating in English, particularly due to a lack of vocabulary, which often led them to rely on dictionaries. The research aimed to determine whether there was a significant difference in reading achievement between tenth-grade students taught using the Power of Two Strategy and those taught with conventional methods at Vocational High School of Muhammadiyah 6 Palembang. A true experimental design was employed, with a sample of 35 students selected through cluster random sampling. Data were collected using pre-tests and post-tests, then analyzed using an independent t-test. The experimental group's average pre-test score was 60, while their post-test score increased to 85. The t-obtained value (5.43) was higher than the t-table value (2.042) at a significance level of 0.05, leading to the rejection of the null hypothesis (Ho) and acceptance of the alternative hypothesis (Ha). These findings indicate a significant improvement in students' reading comprehension when taught using the Power of Two Strategy compared to conventional methods.